Framework for managing deficiencies and inefficiencies in quantity surveying related software implementation - Moorthy Gowthaman; Iresha Gamage; Tania Karunaratne (Construction Economics and Building)
The global construction sector has been revolutionized by information technology although Sri Lankan construction industry continues to be slow to adopt new technologies. Quantity Surveyors encounter deficiencies and inefficiencies when implementing quantity surveying related software within the Sri Lankan construction industry mainly due to the issues related to the product, organization and human resources. Therefore, this study focuses on strategies to overcome deficiencies and inefficiencies in implementing quantity surveying-related software in Sri Lanka and thereby enhance productivity. A qualitative approach was adopted wherein a survey research strategy was followed to investigate the research phenomena in Sri Lanka. The study revealed that lack of financial capacity, lack of standards, lack of skilled personnel, and lack of opportunities to obtain knowledge as deficiencies and less memory access, organizational issues, legal issues, delays, budget overruns and poor product quality as inefficiencies of implementing QS related software in Sri Lanka. Experts’ suggestions highlighted how different stakeholders should act to overcome above mentioned deficiencies and inefficiencies. By incorporating all of the research findings, a framework was created to overcome deficiencies and inefficiencies of implementing new Quantity Surveying software that will assist in the effective advancement of the construction industry.